Risk assessment and triage strategy of cervical cancer primary screening on HPV integration status: 5-year follow-up of a prospective cohort study - Xun Tian; Danhui Weng; Ye Chen; Yi Wang; Xiao Li; Xin Wang; Chen Cao; Danni Gong; Zhen Zeng; Qiongyan Wu; Xueqian Wang; Peng Wu; et al. (Journal of the National Cancer Center)
Objective: We investigated the relation between man papillomavirus (HPV) integration status and the immediate risk of cervical intraepithelial neoplasia (CIN), as well as the triage strategy based on HPV integration test. Methods: 4086 women aged 20 to 65 years in China were enrolled in 2015 for a prospective, population-based, clinical observational study to evaluate the triage performance of HPV integration. Cervical exfoliated cells were collected for HPV testing and cytologic test. If high-risk HPV was positive, HPV integration test was performed at baseline, 2-year and 5-year follow-up. Results: At baseline, HPV integration was positively correlated with the severity of cervical pathology, ranging from 5.0% (15/301) in normal diagnosis, 6.9% (4/58) in CIN1, 31.0% (9/29) in CIN2, 70% (14/20) in CIN3, and 100% (2/2) in cervical cancer (P < 0.001). Compared with cytology, HPV integration exhibits comparable sensitivity and negative predictive value for the diagnosis of CIN3+, higher specificity (92.8% [90.2%–95.4%] vs. 75.5% [71.2%–79.8%], P < 0.001) and higher positive predictive value (36.4% [22.1%–50.6%] vs. 15.2% [8.5%–21.8%], P < 0.001). HPV integration testing strategy yielded a significantly lower colposcopy referral rate than cytology strategy (10.7% [44/410] vs. 27.3% [112/410], P < 0.001). The HPV integration-negative group exhibited the lowest immediate risk for CIN3+ (1.6%) and accounted for the largest proportion of the total population (89.3%), when compared with the normal cytology group (risk, 1.7%; proportion, 72.7%). Conclusion: As a key molecular basis for the development of cervical cancer, HPV integration might be a promising triage strategy for HPV-positive patients.